2017
DOI: 10.3892/etm.2017.4309
|View full text |Cite
|
Sign up to set email alerts
|

GnRH antagonist for patients with polycystic ovary syndrome undergoing controlled ovarian hyperstimulation for in vitro fertilization and embryo transfer in fresh cycles

Abstract: Abstract. The aim of the present study was to evaluate the influence of a gonadotropin-releasing hormone (GnRH) antagonist compared with a GnRH agonist on the in vitro fertilization cycle outcome in patients with polycystic ovary syndrome. The outcomes of pregnancy were evaluated. The area under the curve (AUC) of the receiver operating characteristic (ROC) curve was also used to evaluate whether the endometrial thickness (cm) and estradiol (E 2 ) level (pg/ml) on the day of human chorionic gonadotropin (hCG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…However, the risk of OHSS was lower with the GnRH antagonist. In the present study, the results of the ROC curves demonstrated that neither E 2 nor P level on the day of hCG administration had ideal sensitivity or specificity for predicting clinical pregnancy, in accordance with our previous study (10). Therefore, it appears that in predicting clinical pregnancy rate, the endometrial thickness and estradiol and progesterone levels are not the ideal predictors.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, the risk of OHSS was lower with the GnRH antagonist. In the present study, the results of the ROC curves demonstrated that neither E 2 nor P level on the day of hCG administration had ideal sensitivity or specificity for predicting clinical pregnancy, in accordance with our previous study (10). Therefore, it appears that in predicting clinical pregnancy rate, the endometrial thickness and estradiol and progesterone levels are not the ideal predictors.…”
Section: Discussionsupporting
confidence: 87%
“…When antagonists have been used in patients with normal ovarian function, the clinical pregnancy rate has been reported as lower than that for the agonist protocol, potentially due to the antagonist exerting a negative effect directly or indirectly on endometrial receptivity, for instance by promoting premature maturation of the endometrium (16)(17)(18). It is undesirable that in the present study, there were significant differences in the baseline parameters of age, BMI and FSH hormone profile between the GnRH-A and GnRH-a groups, which differed from similar previous study by our group on polycystic ovary syndrome (10). Cumulative studies have confirmed that an association exists between age and fertility; ovarian aging and reduced ovarian reserve are considered critical factors in determining IVF outcomes (19)(20)(21).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…[ 16 ] The GnRH antagonist has thus presented the IVF-ET a patient-friendly and safe procedure with high efficacy. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%